ANALISIS HUKUM DALAM PUTUSAN MAHKAMAH AGUNG MENGENAI PELECEHAN SEKSUAL TERHADAP ANAK DIBAWAH UMUR (PUTUSAN MAHKAMAH AGUNG NOMOR:865K/PID.SUS/2013) - Eka Rosita; Dessy Artina; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The development of science that affects the development of morality. The behavior of people who are exhibitionistic makes residents nervous because they violate the norms of decency, that is, they prefer minors who are seen as inappropriate which can damage morals and can be traumatic. In the Supreme Court Decision Number 865K / Pid.sus / 2013, there was a decision that acquitted the exhibitionist defendant for sexual abuse of minors and was also proven to have sexually assaulted by holding the child's genitals until their were blisters. However, in the Supreme Court's decision, the Judge decided that the defendant was free from all restrictions. The objectives of this thesis are; First, analysis of legal juridical and theoretical perspectives in the Supreme Court decision regarding sexual harassment of minors (Supreme Court Decision Number: 865k / pid.sus / 2013, second, a form of accountability for criminal acts of sexual harassment. This type of research used in this research is Normative Law Research. This study examines the problem according to the scope and system of the problem through a statutory approach. In this research, the principle used is the error principle, namely Monistic and Dualistic. Monistic view is a view that sees conditions, the existence of a crime must include two things, namely the nature and actions. Meanwhile, the dualistic view is one of criminal acts and criminal liability. From the research, there are two main points that can be rejected. First, from a theoretical perspective, showing off must have the ability to be responsible. Meanwhile, according to a juridical perspective, the Kebumen District Court judges did not consider the Article 44 of the Criminal Code which stipulates that a person who commits an act that cannot be accounted for cannot be convicted because he is considered insane or considered insane. Not bothered by disease. Second, in positive law in Indonesia, the form of criminal responsibility for perpetrators of sexual harassment is in the form of imprisonment and fines. This is stated in Articles 289 and 292 of the Criminal Code and Article 82 of Law Number 35 of 2014 concerning Child Protection. Author's advice, First, it is better for law enforcement officials and government agencies to add articles that regulate the Child Protection Law. The law regarding criminal liability against show-off criminals. Second, it is best if a judge in deciding a case of a criminal act of decency must give punishment to the perpetrator for not regulating his actions.Keywords: Child-Sexual-Abuse